The Efficacy of Gaseous Ozone on some Cariogenic Bacteria - Dukić, Walter (Array, 2013)
The aim of this study is to analyze ozone impact on some cariogenic bacteria in ex vivo and in vitro conditions. The in vitro part of study inoculated dentine with strains of Streptococcus mutans ATCC 33402 and Lactobacillus paracasei ATCC 11974 bacteria. Samples of dentine before and after 40s ozone treatment were collected and anaerobically incubated. Samples of cariogenic dentine (N=24) were collected from permanent molars within the ex vivo segment of the study, prior and after 40s ozone treatment and a number of colonies were counted after incubation. For the in vitro part of study, results have shown a statistically significant average value of reduction of Streptococcusmutans ATCC 33402 and Lactobacillus paracasei ATCC 11974 prior and after ozone treatment (p<0.001). The ex vivo segment of the study has also demonstrated a statistically significant difference in the number of bacteria prior and after ozone implementation (p<0.001). Gaseous ozone demonstrated a strong antimicrobial effect on cariogenic bacteria in both in vitro and ex vivo conditions and it can be used as an adjuvant in caries therapy.